2010
DOI: 10.1073/pnas.1001870107
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and structural analysis of the bacterial magnetic organelle magnetosome using atomic force microscopy

Abstract: The unique ability of magnetotactic bacteria to navigate along a geomagnetic field is accomplished with the help of prokaryotic organelles, magnetosomes. The magnetosomes have well-ordered chain-like structures, comprising membrane-enveloped, nanosized magnetic crystals, and various types of specifically associated proteins. In this study, we applied atomic force microscopy (AFM) to investigate the spatial configuration of isolated magnetosomes from Magnetospirillum magneticum AMB-1 in near-native buffer condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 43 publications
6
53
0
1
Order By: Relevance
“…Imaging rate, 1.03 fps (×20 playback); scan size, 800 × 800 nm 2 [98]. ・Crystallization of a CaCO 3 thin film from supersaturated solution [72] ・Ultrafast imaging of collagen [58] ・Brownian motion & photo-degradation of π-conjugated polyrotaxane [73] ・DNA translocation and looping by type III restriction enzyme [74] ・Biotinylated DNA-streptavidin interaction [75] Miles Miles Shinohara Takeyasu Trimitsu 2008 5 ・Anisotropic diffusion of point defects in streptavidin 2D crystals [76] ・Identification of intrinsically disordered regions of proteins [77] ・Human chromosomes in liquid [78] ・DNA-nuclease interaction [ ・Dynamic equilibrium at the edge of bR 2D crystals [81] ・Structural change of CaM and actin polymerization on streptavidin 2D crystals [82] ・Unidirectional translocation of cellulase along cellulose fibers [83] ・Translocation of EcoRII restriction enzyme along DNA [84] ・Fabrication and imaging of hard material surface [85] ・Purple membrane in contact-mode HS-AFM [86] ・Thermal motion of π-conjugated polymer chain [87] ・Opening of 3D hollow structure of DNA Origami [88] ・Opening of 3D hollow structure of DNA Origami [89] ・ATP-induced conformational change in P2X 4 ・Walking myosin V along an actin filament [91] ・Photo-induced structural change in bR [92] ・2D crystal formation of annexin A-V and height change of p97 [93] ・Analysis of components covering magnesotome surface [94] ・Time course of cell death by antimicrobial peptide [95] ・Dissolution of extreme UV exposed resist films under developing [96] ・Dissolution of extreme UV exposed resist films under developing [97] ・Process of forming supported planar lipid bilayer [98] ・Self assembly of amyloid-like fibrils [99] ・Effect of ClpX on FtsZ polymerization ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging rate, 1.03 fps (×20 playback); scan size, 800 × 800 nm 2 [98]. ・Crystallization of a CaCO 3 thin film from supersaturated solution [72] ・Ultrafast imaging of collagen [58] ・Brownian motion & photo-degradation of π-conjugated polyrotaxane [73] ・DNA translocation and looping by type III restriction enzyme [74] ・Biotinylated DNA-streptavidin interaction [75] Miles Miles Shinohara Takeyasu Trimitsu 2008 5 ・Anisotropic diffusion of point defects in streptavidin 2D crystals [76] ・Identification of intrinsically disordered regions of proteins [77] ・Human chromosomes in liquid [78] ・DNA-nuclease interaction [ ・Dynamic equilibrium at the edge of bR 2D crystals [81] ・Structural change of CaM and actin polymerization on streptavidin 2D crystals [82] ・Unidirectional translocation of cellulase along cellulose fibers [83] ・Translocation of EcoRII restriction enzyme along DNA [84] ・Fabrication and imaging of hard material surface [85] ・Purple membrane in contact-mode HS-AFM [86] ・Thermal motion of π-conjugated polymer chain [87] ・Opening of 3D hollow structure of DNA Origami [88] ・Opening of 3D hollow structure of DNA Origami [89] ・ATP-induced conformational change in P2X 4 ・Walking myosin V along an actin filament [91] ・Photo-induced structural change in bR [92] ・2D crystal formation of annexin A-V and height change of p97 [93] ・Analysis of components covering magnesotome surface [94] ・Time course of cell death by antimicrobial peptide [95] ・Dissolution of extreme UV exposed resist films under developing [96] ・Dissolution of extreme UV exposed resist films under developing [97] ・Process of forming supported planar lipid bilayer [98] ・Self assembly of amyloid-like fibrils [99] ・Effect of ClpX on FtsZ polymerization ...…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the sample after the manipulation can be traced by imaging using the same tip. The use of high-speed AFM in this way has been attempted in a few studies; formation of vacancy defects in streptavidin 2D crystals and 25 subsequent observation of Brownian motion of the defects (as already described in the section 5.2.1.2) [76], breaking actin filaments in the presence of G-actin and subsequent observation of re-polymerization processes [82], breaking microtubules in the presence of tubulin and subsequent observation of re-polymerization processes (unpublished), and removal of magnetosomes from a substrate surface and subsequent observation of molecules transferred from magnetosomes to the surface [94]. Among these studies, a study on actin polymerization is briefly described below.…”
Section: Manipulation and Imagingmentioning
confidence: 86%
“…The TPR domain-containing protein MamA was speculated to play a role in activation of biomineralization (5). It was suggested that MamA self-assembles through its putative TPR domain and concave site to form a large homooligomeric scaffold surrounding the magnetosomes (46,47), whereas its convex site interacts with other magnetosome-associated proteins, like MamC, and several unidentified proteins (46,47). However, as in M. magneticum, the deletion of mamA in M. gryphiswaldense had only a weak effect (5), suggesting that these interactions are not essential or can be partly compensated by other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence microscopy is conventionally used with fluorescent-tagged protein-expressing transformants to analyze target protein localization behaviors in living magnetotactic bacteria. MamA, the protein that is most abundant in magnetosomes and contains 5 sequential tetratricopeptide repeat motifs, is considered to function as a scaffold for bridging other magnetosome proteins (17,28,30). Previous studies revealed that in the exponential-growth phase, MamA shows intracellular linear localization along the long axis of the bacterial cell, whereas in the stationary phase, the protein localizes as 1 or 2 foci.…”
mentioning
confidence: 99%
“…Cellular localization analyses of magnetosome proteins were investigated using transmission electron microscopy (TEM) (26,27), atomic force microscopy (28), and fluorescence microscopy (29). Fluorescence microscopy is conventionally used with fluorescent-tagged protein-expressing transformants to analyze target protein localization behaviors in living magnetotactic bacteria.…”
mentioning
confidence: 99%